Central Serous Chorioretinopathy: Long-Term Results After Photodynamic Therapy - Sousa Pereira, Pedro Nuno (2021)
Introduction: Central serous chorioretinopathy (CSC) is an idiopathic syndrome characterized by neurosensory detachments of the retina. Development of chronic CSC is an indication to treat, and ICGA-guided verteporfin photodynamic therapy has been shown to be very effective.   Our objective was to evaluate the 13-year follow-up of chronic CSC patients treated with standard-fluence PDT and to explore the long-term microstructural and vascular choroidal changes related to the disease and treatment. Methods: Retrospective, interventional case-series analysis was conducted on 18 patients with cCSC, treated with standard PDT. Evaluations were performed every 3 months in the first year, every 6 months during the second year, and annually thereafter. All participants underwent a comprehensive ophthalmic examination. Retinal and choroidal imaging was performed with SD-OCT, SS-OCT, Optomap and OCTA. Results: Twenty-three eyes of eighteen patients were included, with a mean age of 63.9±8.5 years. The mean follow-up was 15.8±1.4 years. The mean number of sPDT treatments was 1.2±0.4. At baseline, subretinal fluid was found in all eyes, RPE proliferation in 9.1% and atrophy in 9.1% of the eyes. There was not a statistically significant improvement in BCVA, despite an initial mean gain of 5.08±10.36 letters at month 12 (p<0.05), which decreased to 1.87±11.9 letters at the end of follow-up. In the final visit, only 3 eyes present subretinal fluid, 3 had fibrosis, but 15 (65.2%) showed atrophy. Central macular thickness reduced from 340.7±114.9 µm to 228.7±38.6 µm at end of the follow-up. The choroid of treated eyes was thicker but the choriocapillaris had less vascular flow compared to fellow-nontreated eyes at this point. Only one session of sPDT was needed in the 19 eyes, and 4 underwent 2 sessions.  Conclusion: ICGA-guided PDT full-fluence is a safe procedure, with no ocular or systemic adverse effects registered in our cohort. After 13 years, only 17.4% required 2 sessions. However, two-thirds of the cases presented atrophy in the last visit, which is probably related to the degenerative course of the disease and limited the initial visual acuity gains in the long term.